Impregnação de cateteres urinários com moduladores de quorum sensing e inibidor de bombas de efluxo para inibição de biofilmes bacterianos associados a infecção do trato urinário - Amando, Bruno Rocha (2018)
Urinary tract infection accounts for 40% of healthcare-related infections and the use of medical devices is an important risk factor for its occurrence. The impregnation with antimicrobial urinary catheters presents good results, but promotes the selective pressure on microorganisms. Thus, the use of quorum sensing modulators and efflux pump inhibitors can be an effective strategy to combat biofilm formation in catheters without causing selective pressure. The objective of this study was to evaluate the in vitro effect of quorum modulators sensing curcumin (CUR) and furaneol (RUF) and the chlorpromazine efflux pump inhibitor (CPZ) impregnated in delay catheters on the formation of biofilms by bacteria associated to urinary tract infection. 18 isolates were used (6 Escherichia coli, 6 Klebsiella pneumoniae and 6 Proteus mirabilis), which were evaluated for sensitivity in the planktonic form, the compounds, by broth microdilution technique. Then the compounds were tested at different concentrations on biofilm formation and on mature biofilms. Subsequently, the catheters were impregnated with solutions containing CUR (1,024 μM), FUR (10,000 μM) or CPZ (400 μg/ml) and the impregnation was evaluated by scanning electron microscopy (SEM). The evaluation of the formation of biofilms in these catheters was performed by counting CFU and the biofilms were evaluated by confocal microscopy. Finally, the effect of ciprofloxacin and meropenem was evaluated in assays with catheters impregnated or not with CPZ. The CUR and FUR didn’t present inhibitory activity on uropathogens, however, the CPZ had MICs ranging from 39.06 to 625 μg/mL. Cur and CPZ inhibited (P <0.05) in vitro biofilm formation. The dispersive energy system associated with scanning electron microscopy demonstrated the effective impregnation of the catheters with CUR, FUR and CPZ. However, only the CPZ-impregnated catheters inhibited (P <0.05) the formation of biofilms by all species. Confocal microscopy demonstrated robust biofilms on non-impregnated catheters and a reduction or absence, in some cases, of biofilms on CPZ-impregnated catheters. Finally, ciprofloxacin and meropenem potentiated the inhibition of biofilm formation (P <0.05) in CPZ-impregnated catheters. Thus, it is concluded that catheter impregnation with the CPZ efflux pump inhibitor may be a promising strategy for the prevention of urinary infections associated with the use of medical devices.